Transformational Leadership in Education: A Review of Concepts, Roles, Challenges, Practices and their Effects - Serey, Mardy; Phon, Sokwin; Hill, Sothea; Sam, Rany; Em, Sereyrath; Pagilagan, Alberto (Indonesian Journal of Education Research (IJoER), 2025)
Purpose of the study: This research aims to review the literature on leadership in comparison to transformational leader practices in education and explore the roles, challenges, and its effects. Methodology: This study presents a comprehensive literature review on transformational leadership in education, examining existing knowledge through a wide array of sources, including books, scholarly articles, reports, and credible online sources. Rather than relying on quantitative data and statistical analysis, this research emphasizes an in-depth exploration of the underlying principles and practical applications of transformational leadership in educational contexts. Main Findings: The findings from this study provide policymakers, educators, scholars, and academics with valuable insights into transformational leadership as a powerful driver of organizational change in education. Transformational leaders, through a clear vision for the future, enable staff to elevate organizational performance by moving from low to high achievement levels. By articulating and fostering a shared purpose, transformational leaders empower their teams to implement strategies that directly improve school outcomes. Transformational leadership in education stands as a powerful tool for driving positive change. By inspiring a shared vision, stimulating intellectual growth, building strong relationships, modeling ethical behavior, and empowering individuals, transformational leaders can create a sustainable and impactful legacy in schools. Novelty/Originality of this study: Unlike the other review, this provides uniquely synthesic comparision of transformation leadership style in Western and ASEAN case studies in education with the integration of transformational leadership practices and adaptation with the context of Industry 4.0.